A nano-sized precipitate strengthened medium entropy alloy with superior strength-ductility synergy and exceptional corrosion resistance. (April 2023) - Pan, Zhimin; Luo, Hong; Cheng, Hongxu; Zhao, Qiancheng; Wang, Xuefei; Fu, Yu; Ma, Yicong; Li, Xiaogang
Abstract: Herein, a novel alloy system, namely CoNiVSix MEAs, was proposed. The addition of Si remarkably promoted strength-ductility synergy, and favourably ameliorated the corrosion resistance of CoNiV MEAs. As for CoNiVSi0.1 MEA, the grain refinement effect prevails in strengthening the MEAs. The improved work-hardening capability caused by the reduction of SFE and the formation of DSBs contributed to a highly sustained strain hardening of CoNiVSi0.1 MEA, which expounded a simultaneous increase in the strength and ductility. Besides, electrochemical results and XPS analyses indicated that CoNiVSi0.1 MEA had better corrosion resistance, and bivalent Si oxides perhaps dominated the film barrier effect from aggressive medium for CoNiVSi0.1 MEA in view of the large atomic ratio of O 2− /OH − and Si/V. This work provides a new and significant approach towards designing corrosion-resistant materials with superior strength-ductility synergy. Graphical abstract: Image 1 Highlights: Si addition achieves strength-ductility synergy and ameliorates the corrosion resistance of CoNiV MEAs. The bivalent Si oxides dominate the film barrier effect from aggressive medium for CoNiVSi0.1 MEA. The lowered SFE and the formation of DSBs contribute to a highly sustained strain hardening of CoNiVSi0.1 MEA.